Ice age animals - Matthews, Rupert; Newman, Colin (New York : Bookwright Press, 1990)
Describes the great Ice Age of the Pleistocene and its effects on the climate, vegetation, animal life, and the world in general.
Includes index.
Bibliography: p. 31.
Keywords: Mammals, Fossil -- Juvenile literature; Glacial epoch -- Juvenile literature; Glacial epoch; Mammals, Fossil